Constructing Mechanochemical Durable Superhydrophobic Composite Coating towards Superior Anticorrosion. Issue 6 (5th November 2021) - Song, Shijie; Yan, Han; Cai, Meng; Huang, Yu; Fan, Xiaoqiang; Zhu, Minhao
Abstract: Corrosion is an inevitable and thorny issue in various fields, resulting in materials degradation, environmental pollution, economic loss, and even emergency safety accidents. Owing to the special surface functions, superhydrophobic coatings are regarded as a promising strategy towards corrosion inhibition. However, the large‐scale and real‐world applications of superhydrophobic coatings are restricted by the mechanical and chemical weaknesses. Herein, a fluorine‐free dual‐layer microarc oxidation/superhydrophobic coating with mechanochemical stabilization is fabricated for corrosion protection. The dual‐layer coating maintains superhydrophobicity under ultraviolet irradiation (15 d), different pH values (1–14), different temperatures (0–100 °C) and abrasion test (180 cycles). Its impedance modulus at the lowest frequency is increased by more than six orders of magnitude than that of the pristine substrate, and the corrosion inhibition efficiency value is calculated as 99.999%. The enhancement of surface multifunctions is attributed to the synergistic effects of microarc oxidation layer and superhydrophobic layer. The as‐prepared robust dual‐layer coating with excellent properties is expected to have potential applications in material protection fields. Abstract : A fluorine‐free dual‐layer superhydrophobic composite coating with excellent mechanochemical durability is reported. Its impedance modulus at the lowest frequency is increased by more than six orders of magnitude than that of the pristine substrate, and the corrosion inhibition efficiency value is calculated as 99.999%. The stable superhydrophobic coating has a great application potential in material protection.